Stein. - Baum, Peter; Bode, Ursula; Bärmann, Matthias; Dittmann, Lorenz; Dobbels, Daniel; Fels, Gilbert; Fried, Erich; Kohl, Ines; Macherhammer, Wolfgang; Morschel, Jürgen; Schwarz, Flor; Sotriffer, Kristian; et al. (München : Bea Voigt Galerie, 1990)
Akiyama, Hiromi ; Baumann, Herbert ; Daucher, Elmar ; Fujiwara, Makoto ; Gerhart, Nikolaus ; Lenassi, Janez ; Nakajima, Osamu ; Naraha, Takashi ; Paszkiewicz, Peter ; Prantl, Karl ; Scheubeck, Anton ; Schneider, Paul ; Seifert, Jiri ; Weissinger, Dagmar
biografie
Stein, Bea Voigt Galerie, München, 14. September bis 30. November 1990
Duits & Engels & Frans
boek